Comparison of Efficacy of Sterile Paper Point, Dentin Harvesting and Pulverization Techniques for Sampling Root Canals using Real Time-PCR: An in Vitro Study - Samad, Tahir Irshad; Dhamodaran, Thokala; H B, Swetha; A S, Aathees; Adiga H, Keerthana; Jaichander, Mrinalini (Journal of Neonatal Surgery, 2025)
Endodontic infections, primarily caused by biofilm-forming bacteria such as Enterococcus faecalis and Streptococcus mutans, pose significant challenges due to their resistance to treatment and host defenses. This study evaluated three sampling techniques—Pulverization, Dentin Harvesting, and Sterile Paper Points—for bacterial recovery and molecular quantification in endodontic research. Sixty sterilized single-rooted human teeth were inoculated with E. faecalis and S. mutans to simulate polymicrobial infections. Bacterial recovery was assessed using colony-forming unit (CFU) counts, while DNA quantification was performed via quantitative PCR (qPCR). Pulverization demonstrated the highest bacterial recovery and DNA yield, attributed to its effective disruption of dentinal biofilms. Dentin Harvesting showed moderate recovery and was valuable for studying microbial distribution within dentin layers. Sterile Paper Points yielded the lowest recovery due to their inability to disrupt biofilms or access bacteria embedded in dentinal tubules. qPCR analysis corroborated these results, with Pulverization being the most efficient technique for both total bacterial and species-specific quantification. These findings emphasize Pulverization as the most effective method for comprehensive microbial analysis, while Dentin Harvesting and Sterile Paper Points offer targeted or surface-level applications. This study highlights the importance of selecting appropriate sampling methods to enhance the accuracy of microbial and molecular analyses in endodontic infections.